OPTIMALISASI PERAN TIM SABER PUNGLI KOTA SAWAHLUNTO DALAM PENCEGAHAN PUNGUTAN LIAR DI SEKTOR PELAYANAN PUBLIK - Siregar, Antoni (Universitas Ekasakti, 2021)
Optimization of the role of the Saber Extortion Team in Sawahlunto City in Combating Illegal Charges in the Public Service Sector has not been optimal because the perpetrators are only given a warning, not action. The role of the Saber Extortion Team is to develop an information technology-based service system to reduce the direct relationship between officers and the community. Second, the Supporting and Inhibiting Factors in the Role of the Saber Extortion Team in Sawahlunto City in Combating Illegal Charges in the Public Service Sector are law enforcement factors. There are law enforcers here, namely the Saber Extortion Task Force who act less professionally because state officials or apparatus as long as they are paid a small salary and have so much authority then illegal levies will continue. There are team members who actually also commit extortion against the perpetrators of extortion they supervise. Furthermore, the factors of facilities and facilities that affect the enforcement of illegal levies in terms of facilities or facilities are incomplete files, lack of communication between institutions, lack of facilities/facilities and the existence of side tasks for members. To support the role of the Task Force, obstacles also come from the community, namely public legal awareness, many people want to report illegal levies but they choose not to report for various reasons.